Add‐on therapy with dapagliflozin under full closed loop control improves time in range in adolescents and young adults with type 1 diabetes: The DAPADream study. Issue 2 (10th December 2020) - Biester, Torben; Muller, Ido; von dem Berge, Thekla; Atlas, Eran; Nimri, Revital; Phillip, Moshe; Battelino, Tadej; Bratina, Natasa; Dovc, Klemen; Scheerer, Markus F.; Kordonouri, Olga; Danne, Thomas
Abstract: Aim: To investigate the effect of the sodium‐glucose co‐transporter‐2 inhibitor dapagliflozin on glucose levels overnight and during the following day after two unannounced meals under full closed loop (FCL) conditions. Materials and Methods: For this single‐centre, double‐blind, randomized, placebo‐controlled, cross‐over trial, non‐obese persons with type 1 diabetes (T1D) were studied twice (10 mg dapagliflozin bid vs. placebo) for 24 hours with two unannounced mixed meal tests 6 hours apart under FCL conditions. Primary outcome was sensor glucose time in range (TIR; 3.9‐10 mmol/L). For safety evaluation, ß‐hydroxybutyrate (BHB), glucagon, insulin and gastric inhibitory polypeptide were measured. Results: Fifteen adolescents (aged 15.4 ± 1.6 years, diabetes duration 10.0 ± 3.4 years, HbA1c 8.4% ± 0.9% [67.7 ± 10.1 mmol/mol]) and 15 young adults (aged 18.7 ± 0.8 years; diabetes duration 12.5 ± 3.6 years; HbA1c 8.3% ± 0.9% [68.5 ± 11.2 mmol/mol]) completed the trial. TIR was significantly higher in the intervention group compared with placebo (68% ± 6% vs. 50% ± 13%; P < .001); nocturnal glucose was significantly lower with dapagliflozin (6.2 ± 0.7 vs. 7.3 ± 1.7 mmol/L; P = .003) without an increase in time at less than 3.9 mmol/L (3.3% ± 6.0% vs 3.1% ± 5.2%; P = .75). Urinary glucose excretion was increased 3‐fold using dapagliflozin (149 ± 42 vs. 49 ± 23 g/24 hours) with a total insulin reduction of 22% (39.7 ± 12.7 vs. 30.6 ± 10.4 U; P = .004). No abnormal elevated BHB values were observed. Conclusions: In adolescents and adults with T1D, dapagliflozin significantly increased TIR on average by 259 minutes/day while reducing glycaemic variability during FCL control without any signs of hypoglycaemia or ketosis.